PEMANFAATAN LIMBAH MATERIAL UNTUK INOVASI ECO GREEN CONCRETE TERHADAP KUAT TEKAN BETON - Lilis Tiyani; Amalia; Sukarman; Afrizal Nursin (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Eco-green concrete uses environmentally friendly materials, substituting traditional aggregates to minimize environmental impact. This study will use a combination of Submerged Arc Welding (SAW), which is the leftover steel welding process, concrete waste, ceramic waste (which substituted coarse aggregate), and rubber waste (which substituted fine aggregate with a portion of waste) to create Eco Green Concrete innovation. SAW 20%, concrete waste 20%, ceramic waste 10%, and rubber waste 8%. Finding out concrete’s compressive strength is the goal of the Eco Green Concrete innovation research. It is predicted that this will result in more affordable project cost estimates without sacrificing the high quality and environmentally friendliness of the concrete utilized. The research was carried out experimentally by making concrete specimens that were tested for compressive strength at the ages of 7, 14, and 28 days. Based on the compressive strength test, the compressive strength test results obtained at 28 days of concrete without innovation were 34.74 MPa and innovation concrete was 33.92 MPa. Based on a comparison of the prices of innovation concrete and conventional concrete per m3, innovation concrete